Faktor yang Mempengaruhi Minat Masuk Perguruan Tinggi bagi Siswa Sekolah Menegah Kejuruan - Alan Febrio; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2022)
This study was carried out to determine how much interest and factors influence college entry for students in class XII of the SMK Electrical Power Installation Engineering Expertise Program at SMK Negeri 1 Tanjung Raya. This study employs descriptive analysis. The study's subjects were 44 students from class XII of the Electrical Power Installation Engineering Expertise Program at SMK Negeri 1 Tanjung Raya. A questionnaire was used to collect data. The validity test of the research instrument is carried out with construction validity, namely by testing the instrument items that have been compiled to experts called validators and using the factor analysis method. The Alpha formula is used to calculate the instrument reliability test based on internal consistency. The amount of interest is analyzed descriptively, and the factors that influence college interest are statistically tested using multiple regression in Excel. According to the study's findings, students in class XII SMK Electrical Power Installation Engineering Expertise Program at SMK Negeri 1 Tanjung Raya have a high interest in continuing their education, with an average percentage of 34%. These interests are influenced by percentage factors, namely the ideals factor (64%), the desire factor (57%), the motivation factor (37%), the family environment (52%), the family economic factor (32%), the relative factor (25%), the teacher factor (32%), the friend factor (36%), the school alumni factor (36%), and the school condition factor (39%).